Low proficiency students: can we help them to speak confidently? - Muriatul Khusmah Musa; Rushita Ismail (UPT Bahasa Universitas Tanjungpura, 2021)
This action research was carried out to find out whether the speaking activities that were done during English lessons could encourage the low proficiency students to speak English confidently. These students admitted that they were afraid of speaking English, particularly in front of their classmates. They had very low self- confidence and felt very anxious when they were asked to speak or present in English. For this research, five speaking tasks were incorporated in the English class with the aim of building up students’ confidence and at the same time encouraging them to speak and participate in the English speaking activities. The five tasks were: self- introduction, fairy tale role-play, open mic, product advertisement campaign and group decision making. These activities were carried out individually as well as in small groups. In short, all the students were given an equal chance to speak English and actively participate as individuals and as group members. Students’ positive responses signify the speaking tasks have helped to reduce their speaking anxiety, build up their confidence in speaking English and improve their speaking skills.